2001
DOI: 10.1128/mmbr.65.1.80-105.2001
|View full text |Cite
|
Sign up to set email alerts
|

PIISignal Transduction Proteins, Pivotal Players in Microbial Nitrogen Control

Abstract: SUMMARY The PII family of signal transduction proteins are among the most widely distributed signal proteins in the bacterial world. First identified in 1969 as a component of the glutamine synthetase regulatory apparatus, PII proteins have since been recognized as playing a pivotal role in control of prokaryotic nitrogen metabolism. More recently, members of the family have been found in higher plants, where they also potentially play a role in nitrogen control. The PII proteins can function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
456
1
13

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(478 citation statements)
references
References 279 publications
5
456
1
13
Order By: Relevance
“…Additional open reading frames in the adjacent regions on either side of the cluster have been tentatively identified as a flavine-containing oxidoreductase (upstream of nifH) and a periplasmic molybdate binding protein plus a molybdenum transporter (downstream of nifN). The order of the M. mazei nitrogen fixation genes is the same as in other diazotrophic methanogenic archaea and differs from most bacterial nif gene clusters in that the two nifI genes are located between nifH and nifD (Sibold et al 1991, Chien and Zinder 1994, Kessler et al 1998, Arcondeguy et al 2001. Phylogenetic analysis of the deduced amino acid sequence of the M. mazei Gö1 nif genes showed that they are most closely related to M. barkeri nif2 genes, suggesting that M. mazei Gö1 has a molybdenum-containing nitrogenase (Table 1).…”
Section: Sequencing and Nucleotide Analysis Of The Nif Gene Cluster Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional open reading frames in the adjacent regions on either side of the cluster have been tentatively identified as a flavine-containing oxidoreductase (upstream of nifH) and a periplasmic molybdate binding protein plus a molybdenum transporter (downstream of nifN). The order of the M. mazei nitrogen fixation genes is the same as in other diazotrophic methanogenic archaea and differs from most bacterial nif gene clusters in that the two nifI genes are located between nifH and nifD (Sibold et al 1991, Chien and Zinder 1994, Kessler et al 1998, Arcondeguy et al 2001. Phylogenetic analysis of the deduced amino acid sequence of the M. mazei Gö1 nif genes showed that they are most closely related to M. barkeri nif2 genes, suggesting that M. mazei Gö1 has a molybdenum-containing nitrogenase (Table 1).…”
Section: Sequencing and Nucleotide Analysis Of The Nif Gene Cluster Fmentioning
confidence: 99%
“…Sequence analysis of this nif gene cluster was performed with the Genetics Computer Group (GCG) software package (Devereux et al 1984), and revealed five genes with sequence similarities to nitrogen fixation genes nifH, nifD, nifK, nifE and nifN. In addition, two genes located between nifH and nifD showed sequence similarities to bacterial glnB genes (Sibold et al 1991, Merrick and Edwards 1995, Arcondeguy et al 2001) and were, therefore, designated nifI 1 and nifI 2 , respectively. Additional open reading frames in the adjacent regions on either side of the cluster have been tentatively identified as a flavine-containing oxidoreductase (upstream of nifH) and a periplasmic molybdate binding protein plus a molybdenum transporter (downstream of nifN).…”
Section: Sequencing and Nucleotide Analysis Of The Nif Gene Cluster Fmentioning
confidence: 99%
See 1 more Smart Citation
“…chlorochromatii CaD3 like cyanobacteria lack GlnD homologs (Arcondéguy et al, 2001). However, differing from cyanobacteria that have only GlnB, Chl.…”
Section: Is Nitrogen Assimilated Via Aladh In Free-living State?mentioning
confidence: 99%
“…4,5 Some mechanisms for amino acid sensing have been documented in bacteria, yeast, and mammals, and potential homologs of such amino acid sensors from other organisms do exist in plants. One example is Glb1, an Arabidopsis homolog of bacterial PII proteins that are considered N "master regulators," [6][7][8][9] although the role of Glb1 seems to be constrained compared with the bacterial counterparts. 10 Likewise, Arabidopsis homolog of Target of Rapamycin (TOR) plays a role in integrating nutrition signals including nitrogen in a similar manner as its yeast and animal counterparts.…”
Section: Introductionmentioning
confidence: 99%